Monitoring Dan Evaluasi Sistem Inovasi Daerah (SIDa) Kota Surakarta Tahun 2023 - Aris Setiawan; Rony Widjanarko (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
Law 23 of 2014 concerning regional government CHAPTER XXI Articles 386 to Article 389 emphasizes regional innovation. This affirmation is a form of breakthrough to deal with slow and monotonous bureaucratic conditions and to fight all forms of constancy and comfort zones which have produced a less productive work culture (Adler, 1999). With innovation in the administration of regional government, it is hoped that old ways of governing must be changed through government reform1. The rationale for regulating innovation in Law Number 23 of 2014 includes: (1) regions must provide services and welfare to the community as a manifestation of regional autonomy; (2) there is an increase in regional competitiveness, which will linearly encourage national competitiveness in the international arena. Moreover, in today's free market competition, national competitiveness has become an attraction and measuring force for global competition in the trade and investment sectors; (3) innovation is the key to accelerating improvements in competitiveness considering that globally Indonesia's current condition is not very good when compared with other countries, especially in ASEAN.